The importance of environment protection for the safety of civil population - Justyna Stochaj (Nowoczesne Systemy Zarządzania, 2021)
The paper is devoted to the presentation of the importance of environmental protection for the safety of civilians. It was divided into five parts. The first contains a brief introduction. The second defines the con-cept of environmental protection and presents a list of its threats. The third part is devoted to presenting the possible consequences of the lack of environmental protection for humans. In the fourth part selected concepts of environmental protection are characterized. The fifth part contains a summary.